Pembudayaan Agama Dalam Pembentukan Karakter Siswa Di MTs Negeri Sleman Kota Yogyakarta - Fil Isnaeni (SAP (Susunan Artikel Pendidikan), 2018)
The background of the research is the moral problems related to the the nation’s characters that occur in Indonesia due to the erosion of religious values resulting from the change of times that is damaging the morale of the students and nation. Education plays a role in shaping student’s good characters. Public Madrasah Tsanawiyah in Sleman, Yogyakarta cultivates religion to form student’s good characters. This research is expected to contribute to the education in providing students with good characters inherent in the student's personality through the habituation process. It is a field research that uses a qualitative descriptive analysis. Research data are collected by observation, interview, and documentation. The data are analyzed by reviewing data, reducing data, coding, checking the validity of data and then drawing a general conclusion from the specifically-studied data